PENERAPAN PERJANJIAN KERJA WAKTU TERTENTU (PKWT) TERHADAP PEKERJA OUTSOURCING PASCA PUTUSAN MK NO. 27/PUU-IX/2011 (Lex Jurnalica, 2016)
AbstractThe employment agreement is the beginning of the birth of the industrial relations between employers and workers. Lately many companies that use Work Agreement Specific Time (PKWT) to reduce the cost of labor in order to increase profits. It's just that in practice many PKWT system implementation that does not comply with the provisions of Law No. 13 of 2003 on Labour, to the detriment and eliminate the protection of workers / laborers. The problem in this research is how the legal protection for workers / laborers PKWT and how settlement / solution by employers in the face of obstacles or dispute on the implementation PKWT by the decision of the Court No.27 / PUU-IX / 2011. If done in accordance with existing rules, there is already adequate protection to workers / laborers PKWT, it's just that in practice there are still many obstacles due to the vagueness of the rules on the application of PKWT, resulting in a deviation from the implementation of the implementation of the protection of the workers / laborers Labor Agreement Certain time. The obstacles encountered in the implementation of the employment agreement specified time (PKWT) on the protection of workers / laborers among others, the difficulties associated with the regulations and constraints related to labor agreements. The solution in case of dispute is to conduct dispute resolution outside the court and if it can not be resolved out of court, the matter will be brought to justice. Keywords: Legal Protection-PKWT AbstrakPerjanjian kerja merupakan awal dari lahirnya hubungan industrial antara pengusaha dengan pekerja. Akhir-akhir ini banyak perusahaan yang memakai Perjanjian Kerja Waktu Tertentu (PKWT) untuk menekan biaya buruh demi meningkatkan keuntungan. Hanya saja dalam prakteknya banyak penerapan sistem PKWT yang tidak sesuai dengan ketentuan dalam Undang-undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan, sehingga merugikan dan menghilangkan perlindungan terhadap pekerja/buruh. Masalah dalam penelitian ini adalah bagaimana perlindungan hukum terhadap pekerja/buruh PKWT dan bagaimana penyelesaian/solusi yang dilakukan oleh pengusaha dalam menghadapai kendala atau sengketa pada pelaksanaan PKWT berdasarkan adanya putusan MK No.27/PUU-IX/2011. Jika dilakukan sesuai dengan aturan yang ada, memang sudah terdapat perlindungan yang memadai terhadap pekerja/buruh PKWT, hanya saja dalam pelaksanaannya masih terdapat berbagai halangan yang disebabkan oleh ketidakjelasan aturan tentang penerapan PKWT, sehingga terjadi penyimpangan terhadap penerapan pelaksanaan perlindungan terhadap pekerja/buruh Perjanjian Kerja Waktu Tertentu. Kendala-kendala yang dihadapi dalam pelaksanaan perjanjian kerja waktu tertentu (PKWT) terhadap pemberian perlindungan pekerja/buruh diantaranya adalah, kendala yang berkaitan dengan peraturan dan kendala yang berkaitan dengan perjanjian kerja. Solusinya jika terjadi sengketa yaitu dengan melakukan penyelesaian sengketa diluar pengadilan dan jika tidak dapat diselesaikan diluar pengadilan, masalah tersebut akan dibawa ke pengadilan. Kata kunci:   Perlindungan Hukum-PKWT